Tecnologias digitais e a prática de home office na pandemia da Severe Acute Respiratory Syndrome – Coronavirus 2 (SARS-COV-2) - Oliveira , Kelly Vanessa de (2021)
With the coronavirus pandemic (SARS-CoV-2), the home office was implemented in most private companies and public institutions in Brazil and in the world, aiming at sustaining economic activity and the continuity of the provision of services to society. This reality may have been possible due to technological advances, expanded since the 21st century, that made it possible increasing the number of functions of technological tools, that allowed the use of devices in the execution of various activities, including work activities. However, for most public servants, remote work represented a new universe, considering that it was put into practice without prior planning by the Public Administration and responsible institutions. Therefore, this paper has as its main contribution to verify the effects of the home office in the execution of activities carried out by public servants at UFPB. The collection instrument sought to contemplate aspects related to access to technology, task management, communication, and the association of this type of work to some type of health problem and its nature. The random sample has 66 cases. The analysis of the responses received was performed using statistical methods, such as the Pearson and Spearman correlation coefficients, used in order to investigate variables related to work that could influence the variables related to the health of the public servant. In addction Paraconsistent Logic was used for qualitative assessment of the degree of agreement of respondents regarding the statements made. Some aspects of the conclusion resulting from data analysis confirmed what the theory advocates, such as the importance of focused meetings to encourage participation and the emergence of innovations. The analyzed data also revealed that, in general, the servers do not have an environment in their homes with the relevant conformation for the execution of work tasks, and the changes brought about in the work contexts arising from telework, the overload of activities, the increase the use of technological devices and the inadequacy of the work position were worrisome due to the associations made with health risks. The research also revealed that the servers made use of various means of communication, such as WhatsApp messages, email and videoconference, and that these proved to be effective, showing that the context of the pandemic, together with the experience of the home office, made it possible to see how society is inserted in the digital universe, allowing a greater exchange of information and knowledge, characteristic of the network society, provided by the popularization of the Internet, with technology being the fundamental basis for communication and carrying out activities away from the physical work environment.